The legend of Bagger Vance - Redford, Robert; Nozik, Michael; Eberts, Jake.; Leven, Jeremy; Smith, Will, 1968-; Damon, Matt.; Theron, Charlize; Ballhaus, Michael, 1935-; Graham, Angelo; Graham, W. Steven; Corwin, Hank.; Portman, Rachel; et al. (Universal City, CA : DreamWorks Home Entertainment, 2001)
The protagonist of this metaphysical fable is Rannulph Junah, Southern aristocrat and World War I hero. In a tournament in Savannah, he defeats two golf pros by following the teachings of his guru, Bagger Vance, a black mystic serving as his caddie.
Based on the novel "The legend of bagger Vance" by Steven Pressfield.
Videodisc release of the 2000 motion picture.
Special features: Robert Redford: Insight into The legend of Bagger Vance ; production featurette ; theatrical teaser trailer ; theatrical trailer ; production notes ; cast and filmmaker biographies.
Director of photography, Michael Ballhaus ; art directors, Angelo P. Graham, W. Steven Graham ; editor, Hank Corwin ; music, Rachel Portman ; costume designer, Judianna Makovsky ; production designer, Stuart Craig.
Will Smith, Matt Damon, Charlize Theron.
MPAA rating: PG-13.
Keywords: Golfers -- Drama; Caddies -- Drama; African American men -- Drama; Supernatural -- Drama; Positive psychology; Feature films; Films for the hearing impaired